Trends in Quality and Quantity of Dietary Intake from Full-Service Restaurants and Fast Food Restaurants Among US Adults, 2003–2016 (P04-147-19). (13th June 2019) - Liu, Junxiu; Rehm, Colin; Micha, Renata; Mozaffarian, Dariush
Abstract: Objectives: Meals from full-service restaurants (FS) and fast-food restaurants (FF) are major contributors to US diets. Yet, their overall healthfulness, trends, and disparities are unknown. We sought to evaluate trends in FS and FF diet quality in US adults, and disparities by key subgroups. Methods: We used data from 7 NHANES cycles 2003–2016, totaling 35, 015 adults aged 20 + y. Percent of energy (%E) and meal settings (breakfast, etc.) from FS and FF were examined. Diet quality was based on the validated American Heart Association (AHA) 2020 primary diet score (components: fruits/vegetables, whole grains, fish/shellfish, sugar-sweetened beverages, sodium; range 0–50) and secondary score (adding nuts/seeds/legumes (NSL), processed meat, saturated fat; range 0–80). Analyses utilized survey-weight with energy adjusted to 2000 kcal/d. Results: Between 2003–16, US adults consumed ∼9%E from FS (8.5% in 2003–04; 9.5% in 2015–16, p trend = 0.38) and ∼12%E from FF (10.5%; 13.4%; p trend = 0.31). Over this period, increasing FF meals were eaten for breakfast (4.4% to 7.6%) (p trend < 0.001). In 2015–16, diet quality of both FS and FF were low: mean primary AHA score of 17.3 and 14.7 (out of 50), respectively; and secondary AHA score of 31.6 and 27.6 (out of 80). Between 2003–16, diet quality of FS was unchanged; while FF quality was unchanged per the primary score and modestly improved per the secondary score (improvement of 4.2%; p trend < 0.001), largely due to changes in NSL and saturated fat. The % of FF meals with poor quality (<40% adherence to the AHA secondary score) declined from 74.6% to 69.8%, while the % with intermediate quality (40–79.9% adherence) increased from 25.4% to 30.2% (both p trend < 0.001) (Figure). FS meals with poor (∼50%) and intermediate (∼50%) quality were stable over time. Notably,  < 0.1% of consumed FS or FF meals met ideal quality ( > 80% adherence). Disparities in FS and FF meal quality were observed by race/ethnicity, income, and education, which generally worsened over time. Conclusions: FF and FS meals provide 1 in 5 calories in US adults. Modest improvements in quality were observed in FF, but not FS; average quality for both remained low, with growing disparities. These findings highlight specific challenges and opportunities for improving quality of restaurant meals in the US. Funding Sources: AHA, NIH/NHLBI. Supporting Tables, Images and/or Graphs: